COVID-19 and ECT – a Victorian perspective. (October 2021) - Jagadheesan, Karuppiah; Walker, Frances; Danivas, Vijay; Itrat, Quratulain; Lakra, Vinay
Objectives: (i) to describe the operational strategies implemented to practise electroconvulsive therapy (ECT) safely, and (ii) to explore the effect of the lockdown and operational strategies on the characteristics of patients who received ECT during the initial 6 months of the COVID-19 lockdown. Methods: At first, the operational strategies that were implemented at the Broadmeadows ECT suite were summarised. Subsequently, the characteristics of patients who received ECT in the lockdown period (16 March–16 September 2020) and in the comparison period (16 March–16 September 2019) were compared. Results: Many safety measures were implemented, and there was no COVID-19 infection among mental health staff and patients. In the lockdown period, the number of patients (23.9%) and the total number of ECTs (29.4%) were less. This pattern was more prominent among the aged patients. Conclusion: Safe practices are essential to provide ECT during lockdowns even when the community transmission of COVID-19 is high.